Organic haloamines in chlorine-based disinfected water systems: A critical review - How, Z.; Kristiana, I.; Busetti, F.; Linge, Kathryn; Joll, C. (2016)
This paper is a critical review of current knowledge of organic chloramines in water systems, including their formation, stability, toxicity, analytical methods for detection, and their impact on drinking water treatment and quality. The term organic chloramines may refer to any halogenated organic compounds measured as part of combined chlorine (the difference between the measured free and total chlorine concentrations), and may include N-chloramines, N-chloramino acids, N-chloraldimines and N-chloramides. Organic chloramines can form when dissolved organic nitrogen or dissolved organic carbon react with either free chlorine or inorganic chloramines. They are potentially harmful to humans and may exist as an intermediate for other disinfection by-products. However, little information is available on the formation or occurrence of organic chloramines in water due to a number of challenges. One of the biggest challenges for the identification and quantification of organic chloramines in water systems is the lack of appropriate analytical methods. In addition, many of the organic chloramines that form during disinfection are unstable, which results in difficulties in sampling and detection. To date research has focussed on the study of organic monochloramines. However, given that breakpoint chlorination is commonly undertaken in water treatment systems, the formation of organic dichloramines should also be considered. Organic chloramines can be formed from many different precursors and pathways. Therefore, studying the occurrence of their precursors in water systems would enable better prediction and management of their formation.